Phenotypic characteristics of F64L, I68L, I107V, and S77Y ATTRv genotypes from the Transthyretin Amyloidosis Outcomes Survey (THAOS) - Gentile, Luca; Diemberger, Igor; Plante-Bordeneuve, Violaine; Mazzeo, Anna; Dori, Amir; Luigetti, Marco; Paolantonio, Andrea Di; Dispenzieri, Angela; Grogan, Martha; Cruz, Márcia Waddington; Adams, David; Inamo, Jocelyn; et al. (PLOS ONE, 2024)
Transthyretin amyloidosis (ATTR amyloidosis) is a progressive, multi-systemic disease with wild-type (ATTRwt) and hereditary (ATTRv) forms. Over 130 variants associated with ATTRv amyloidosis have been identified, although little is known about the majority of these genotypes. This analysis examined phenotypic characteristics of symptomatic patients with ATTRv amyloidosis enrolled in the Transthyretin Amyloidosis Outcomes Survey (THAOS) with four less frequently reported pathogenic genotypes: F64L (c.250T>C, p.F84L), I68L (c.262A>T, p.I88L), I107V (c.379A>G; p.I127V), and S77Y (c.290C>A; p.S97Y). THAOS is the largest ongoing, global, longitudinal observational study of patients with ATTR amyloidosis, including both ATTRwt and ATTRv amyloidosis. This analysis describes the baseline demographic and clinical characteristics of untreated symptomatic patients with the F64L, I68L, I107V, or S77Y genotypes at enrollment in THAOS (data cutoff date: January 4, 2022). There were 141 symptomatic patients with F64L (n = 46), I68L (n = 45), I107V (n = 21), or S77Y (n = 29) variants at the data cutoff. Most patients were male and median age at enrollment was in the sixth decade for S77Y patients and the seventh decade for the others. A predominantly neurologic phenotype was associated with F64L, I107V, and S77Y genotypes, whereas patients with the I68L genotype presented with more pronounced cardiac involvement. However, a mixed phenotype was also reported in a considerable proportion of patients in each variant subgroup. This analysis from THAOS represents the largest study of ATTRv symptomatic patients with the F64L, I68L, I107V, and S77Y genotypes. These data add to the limited knowledge on the clinical profile of patients with specific ATTRv variants and emphasize the importance of comprehensive assessment of all patients. Trial registration ClinicalTrials.gov: NCT00628745.
Gesehen am 08.10.2024